2022
DOI: 10.3389/fbioe.2022.994711
|View full text |Cite
|
Sign up to set email alerts
|

Engineering constructed of high selectivity dexamethasone aptamer based on truncation and mutation technology

Abstract: Various biosensors based on aptamers are currently the most popular rapid detection approaches, but the performance of these sensors is closely related to the affinity of aptamers. In this work, a strategy for constructed high-affinity aptamer was proposed. By truncating the bases flanking the 59 nt dexamethasones (DEX) original aptamer sequence to improve the sensitivity of the aptamer to DEX, and then base mutation was introduced to further improve the sensitivity and selectivity of aptamers. Finally, the 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…The results showed that hydrocortisone, cortisone, prednisone, prednisolone, and betamethasone exhibited a CR of 23.8, 0.9, 43.1, 41.0, and 92.5%, respectively, whereas progesterone and hydroxy progesterone caproate showed no CR with DXMS (Figure S3A, Table S1). These results were similar to the previous study . The presence of different CRs might stem from the different structural similarities between these structural analogues and DXMS (Table S1), leading to differences in the structure of the Ag recognition site.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The results showed that hydrocortisone, cortisone, prednisone, prednisolone, and betamethasone exhibited a CR of 23.8, 0.9, 43.1, 41.0, and 92.5%, respectively, whereas progesterone and hydroxy progesterone caproate showed no CR with DXMS (Figure S3A, Table S1). These results were similar to the previous study . The presence of different CRs might stem from the different structural similarities between these structural analogues and DXMS (Table S1), leading to differences in the structure of the Ag recognition site.…”
Section: Resultssupporting
confidence: 91%
“…These results were similar to the previous study. 33 The presence of different CRs might stem from the different structural similarities between these structural analogues and DXMS (Table S1), leading to differences in the structure of the Ag recognition site. Overall, the method has a broad spectrum of detection and can simultaneously detect five glucocorticoid drugs.…”
Section: Analyticalmentioning
confidence: 99%
“…Modulation of the affinity between an aptamer and target is usually achieved by direct mutation of the nucleic acid sequence, including base substitutions, truncation of the aptamer strand, and so on. However, the aptamer sequence mutation-based approach is both time-consuming and inefficient. In contrast, our previous work demonstrated that it is possible to combine the two recognition elements through a strategy of coupling aptamers and peptides to simply and conveniently increase affinity by increasing the binding sites . This strategy involves a simple copper-catalyzed alkyne azide cycloaddition (CuAAC) synthesis technique, which can effectively solve the complex process of peptide and aptamer coupling.…”
Section: Introductionmentioning
confidence: 99%